2015
DOI: 10.2174/1874213001508010040
|View full text |Cite
|
Sign up to set email alerts
|

Remediation of Polar Ecosystems Polluted by Gas Condensate and Oil Hydrocarbons by Biological Preparations

Abstract: Assessment of degradation of gas condensate and oil hydrocarbons in a sample of soil illuvial horizon as Polar ecosystems part and soil model for degradation under action of new biological preparations (Bioros and Piksa) in experimental conditions showed that degradation of gas condensate in soil, for example, under Bioros action was faster than degradation of oil. After application of Piksa the process of oil degradation in soil was much faster. The activity of catalase and dehydrogenase enzymes increased wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 2 publications
0
4
0
Order By: Relevance
“…The proposed solutions include the application of compost (Mehta et al 2014 ; Wyszkowska and Wyszkowski 2006 ; Wyszkowski and Ziółkowska 2013 ), urea (Komilis et al 2009 ; Wyszkowska et al 2006 ), finely ground straw, sawdust (Wyszkowska et al 2002 ), biological preparations (Galiulin and Galiulina 2015 ) and whey (Jonsson and Östberg 2011 ). In a study by Galiulin and Galiulina ( 2015 ), biocompost and biopreparations enabled almost complete degradation of hydrocarbons from crude oil and gas condensate. The effectiveness of remediation was evaluated based on, among others, dehydrogenase activity, and the research findings have been applied in practice ( Patent of the Russian Federation, RU2387996 (C1) ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The proposed solutions include the application of compost (Mehta et al 2014 ; Wyszkowska and Wyszkowski 2006 ; Wyszkowski and Ziółkowska 2013 ), urea (Komilis et al 2009 ; Wyszkowska et al 2006 ), finely ground straw, sawdust (Wyszkowska et al 2002 ), biological preparations (Galiulin and Galiulina 2015 ) and whey (Jonsson and Östberg 2011 ). In a study by Galiulin and Galiulina ( 2015 ), biocompost and biopreparations enabled almost complete degradation of hydrocarbons from crude oil and gas condensate. The effectiveness of remediation was evaluated based on, among others, dehydrogenase activity, and the research findings have been applied in practice ( Patent of the Russian Federation, RU2387996 (C1) ).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, one may conclude that compost can accelerate the microbiological degradation of petroleum-derived contaminants, because it constitutes a source of necessary cosubstrates, nutrients or microorganisms, including the following: mesophilic and thermophilic bacteria, actinobacteria and fungi (Mehta et al 2014 ). Galiulin and Galiulina ( 2015 ), who investigated the effects of biopreparations in soil contaminated with oil at 50 g kg −1 , reported a significant increase in dehydrogenase activity. In soil supplemented with Bioros (0.5 g kg −1 ), which contains two groups of microorganisms: Rodococcus sp.…”
Section: Discussionmentioning
confidence: 99%
“…Other authors also demonstrated the destructive effect of petroleum-derived products on the biochemical properties of soil [ 75 , 125 , 126 ]. Taking into account the resistance (RS) of enzymes to diesel oil, Wyszkowska et al [ 23 ] ordered them as follows (in descending order from the most to the least resistant): Glu > Pac > Aryl > Pal > Ure > Cat > Deh, whereas considering their resistance to unleaded petrol, their order was: Pac > Glu > Cat > Aryl > Deh > Pal > Ure.…”
Section: Discussionmentioning
confidence: 99%
“…As for bacteria, the following genera are dominant: Bacillus (Bento et al 2005 ; Fatima et al 2015 ), Pseudomonas (Fatima et al 2015 ), Staphylococcus (Moscoso et al 2012 ; Silva et al 2015 ), Acinetobacter (Chang et al 2011 ; Mnif et al 2015 ) and Paenibacillus (Lipińska et al 2015 ), while as regards fungi, the following genera predominate: Aspergillus (Diaz-Ramirez et al 2013 ; El-Hanafy et al 2017 ) and Candida (Fan et al 2014 ; Silva et al 2015 ). These products can also be removed from soil by, inter alia, biostimulation of autochthonous microorganisms (Adam et al 2017 ; Fan et al 2014 ), bioaugmentation (Chang et al 2011 ; Fan et al 2014 ; Galiulin and Galiulina 2015 ; Semrany et al 2012 ), phytoremediation (Agnello et al 2016 ; Sivitskaya and Wyszkowski 2013 ; Soleimani et al 2010 ) and electro-bioremediation (Shrestha et al 2010 ; Yuan et al 2016 ; Wang et al 2012 ). It is important, however, to observe the response of both cultured microorganisms (Kucharski and Jastrzębska 2005 ; Soleimani et al 2010 ; Wyszkowska et al 2015 ) to soil contamination and the enzymes of importance in terms of soil quality, i.e.…”
Section: Introductionmentioning
confidence: 99%